The higher prevalence of truncal obesity and diabetes in American than Chinese patients with chronic hepatitis C might contribute to more rapid progression to advanced liver disease. Issue 8 (22nd August 2017) - Rao, H.; Wu, E.; Fu, S.; Yang, M.; Feng, B.; Lin, A.; Fei, R.; Fontana, R. J.; Lok, A. S.; Wei, L.
Abstract : Summary: Background: Chronic hepatitis C virus (HCV) infection is the leading cause of cirrhosis and hepatocellular carcinoma (HCC) in the United States (US) and an emerging cause in China. Aim: To compare the clinical characteristics of hepatitis C patients in the US and China, and factors influencing disease stage. Methods: Prospective study of 2 cohorts of HCV patients recruited at 1 site in the US and 3 sites in China. Standardised questionnaire on risk factors and medical history were used and diagnosis of cirrhosis and HCC was based on pre‐defined criteria. Results: One thousand nine hundred and fifty seven patients (1000 US and 957 China) were enrolled. US patients were more likely to be men (61.4% vs 48.5%), older (median age 57 vs 53 years), obese (38.4% vs 16.8%) and diabetic (21.8% vs 10.8%). A significantly higher per cent of US patients had cirrhosis (38.2% vs 16.0%) and HCC (14.1% vs 2.7%). Investigator estimated time at infection in US was 10 years earlier than in Chinese patients but US patients were more likely to have advanced disease even after stratifying for duration of infection. Study site in the US, older age, truncal obesity, diabetes and prior HCV treatment were significant predictors of advanced disease on multivariate analysis. Conclusions: HCV patients in the US had more advanced liver disease than those in China. We speculate that underlying fatty liver disease may be a major contributor to this difference, and management of glycometabolic abnormalities should occur in parallel with anti‐viral therapy to achieve optimal outcomes.